(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2016)
Monitoring of the conditions and development trends of the milk and dairy products market in Ukraine. The results of monitoring of conditions and development trends of milk and dairy products market in Ukraine are represented in the article. Here is done the overview of actual issues of the Ukrainian dairy industry functioning. Author has conducted the estimation of the volume of milk and milk products consumption in the whole country and by regions. The analysis of the balance and the dynamics of supply and demand on the main types of dairy products and the estimating of the domestic and foreign markets capacity are done. Author has determined the factors affecting on the volume of consumption, demand and supply in the milk and dairy products market. Dynamic of milk and dairy products production in terms of its basic types is explored. Here is also conducted the dynamic of exports of the main dairy products types in recent years. The possibilities and directions of domestic milk market regulation are defined. Author has formulated priority organizational and economic measures for enhancing of Ukrainian milk enterprises export potential.